Soleus muscle flap for the coverage of pre-tibial defect of middle third of leg - Satter, Tahmina; Khan, Md Noazesh; Awwal, Rayhan (Bangladesh Journal of Plastic Surgery, 2014)
Soft tissue defects of the lower limb are a challenge to the plastic surgeon but a soleus muscle flap often provides the solution. Early reconstruction by soft tissue to cover exposed bone significantly reduces the risk of infection, nonunion and subsequent amputation. A Prospective, observational study was carried out in the Department of Plastic Surgery & Burn Unit, Dhaka Medical College Hospital and Department of Plastic Surgery, National Institute of Traumatology and Orthopaedic Rehabilitation, Dhaka, from September 2011 to March 2013. 30 cases were selected by purposive continuous sampling who had soft tissue defect in front of the middle third of the legs only. Proximally based soleus muscle transposition flap was done by standard operative procedure under spinal anaesthesia or general anaesthesia and under tourniquet control. After 2 months of operation, final follow-up was done. Regarding the outcome of flap surgery, 18 (60%) cases were found excellent. 7 (23.33%) cases were good, 3 (10%) were fair and 2 (6.66%) were poor. In the final follow up, according to the preset criteria for evaluation of wound coverage by soleus muscle flap, the satisfactory result (excellent and good) was 83.33%. Unsatisfactory (fair and poor) result was in 16.67% cases. Effective coverage of pretibial defect of middle third of leg by soleus muscle flap with satisfactory outcome was seen in this study. DOI: http://dx.doi.org/10.3329/bdjps.v4i1.18685 Bangladesh Journal of Plastic Surgery January 2013, 4(1): 10-15